Evolving genomic approaches to the study of complex cardiovascular diseases in human populations: genetic and genomic epidemiology - O'Donnell, Christopher (Henry Stewart Talks, 2007)
Cardiovascular disease (CVD) as the leading cause of death in the Western world, Role of long-term exposure to risk factors prior to disease manifestation, Common CVDs: myocardial infarction, stroke, congestive heart failure and sudden cardiac death, Complex traits with both genetic and environmental risk factors, The Human Genome Project and the HapMap Project, Genetic linkage families, Genome-wide studies of Single Nucleotide Polymorphisms (SNPs), Drug development and predictive testing
Archived at 2018/05/31